Conceptions of Giftedness and Talent 2020
DOI: 10.1007/978-3-030-56869-6_2
|View full text |Cite
|
Sign up to set email alerts
|

Talent Development, Cultural Diversity, and Equity: The Challenge of the Andean Countries

Abstract: Is it possible to identify gifted children in the extreme highlands of the Andes or in the depth of the Amazon jungle? This is the core question of my academic life. It was first asked as a provocative question on July 1991, while I was attending the Educational Research Workshop Education of the Gifted in Europe: Theoretical and Research Issues, a milestone event for gifted education in Europe (Mönks & Pflüger, 2005). At that moment, my country was immersed in a bloody armed conflict, and gifted education was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…From a developmental standpoint, both academics and administrative staff must consider cognitive and conative elements, as well as access to university facilities, to obtain exceptional results. Blumen (2021) revealed that despite their high levels of stress, young scholars from ethnically diverse backgrounds who were studying at a culturesensitive university were engaged with their studies and maintained their academic achievement. Academics and administrative employees appear to be supported by the university.…”
Section: Introductionmentioning
confidence: 99%
“…From a developmental standpoint, both academics and administrative staff must consider cognitive and conative elements, as well as access to university facilities, to obtain exceptional results. Blumen (2021) revealed that despite their high levels of stress, young scholars from ethnically diverse backgrounds who were studying at a culturesensitive university were engaged with their studies and maintained their academic achievement. Academics and administrative employees appear to be supported by the university.…”
Section: Introductionmentioning
confidence: 99%